“Contextualization” in development: a microgenetic study of an English as a Foreign Language teacher - Paola Gabriella Biehl; Adriana de Carvalho Kuerten Dellagnelo (Fórum Linguístico)
In the field of English as a Foreign Language (EFL) teacher education, attention must be given to novice teachers, so that they can establish a dialectical relation between theory and practice aiming at praxis. Following one of the tenets of Vygotsky's (1987) Sociocultural theory, this study aimed to trace a novice teacher's developmental path, as she was mediated by a more experienced other. The guiding question that permeated this study was the extent to which the mediating sessions between teacher educator and novice teacher impacted the teacher’s development of the concept “contextualization”. Qualitative research methods were used to analyze data, which were collected through class observation and mediating sessions, both videotaped.  The findings suggest the importance of the teacher educators’ intentional and goal-oriented mediation for the participant teacher.